Sensors: A Monolithically Processed Rectifying Pixel for High‐Resolution Organic Imagers (Adv. Electron. Mater. 6/2018). (12th June 2018) - Zalar, Peter; Matsuhisa, Naoji; Suzuki, Toshiki; Enomoto, Shintaro; Koizumi, Mari; Yokota, Tomoyuki; Sekino, Masaki; Someya, Takao
Abstract : Passively addressed imaging arrays are challenging to make, since photodiodes lose their rectifying properties upon illumination. Thus, the integration of a switching element with the sensor is crucial for the realization of image sensors and other "sensing surfaces". A monolithically processed rectifying pixel is described by Peter Zalar, Takao Someya, and co‐workers in article number1700601 . The described method allows for high pixel densities and excellent imaging performance without the need of transistors.